2003
DOI: 10.2334/josnusd.45.107
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori in recurrent aphthous ulceration by nested PCR

Abstract: Recurrent aphthous ulceration (RAU) is the most common lesion of the oral mucosa. Although many factors have been postulated as etiological factors for RAU, the role of Helicobacter pylori as a causative agent of RAU remains controversial. We therefore investigated the association of H. pylori and RAU by a highly sensitive technique, nested polymerase chain reaction (PCR), in 22 patients with RAU with ages ranging from 12-36 years. Samples were brushed from the lesions and the dorsum of the tongue of each pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Recently, H. pylori has been considered as a causative factor for RAS as well as many other dermatological disorders such as urticaria, rosacea, lichen planus, Behçet's disease, and atopic dermatitis. It has been speculated that H. pylori may cause mucosal injury by inducing lymphocyte‐derived chemokines resulting local neutrophil accumulation and release of proteolytic enzymes and oxygen radicals 1–3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, H. pylori has been considered as a causative factor for RAS as well as many other dermatological disorders such as urticaria, rosacea, lichen planus, Behçet's disease, and atopic dermatitis. It has been speculated that H. pylori may cause mucosal injury by inducing lymphocyte‐derived chemokines resulting local neutrophil accumulation and release of proteolytic enzymes and oxygen radicals 1–3 …”
Section: Discussionmentioning
confidence: 99%
“…Many genetical, immunological, physical, psychological, and microbiological factors have all been considered as causative subjects. In recent years, H. pylori has been suggested as one of the important etiological agents in the pathogenesis of RAS 1–4 …”
Section: Introductionmentioning
confidence: 99%
“…Many facts have suggested that oral cavity is a reservoir of the organism. Oral cavity is a possible route of transmission to other sites (Anak Iamaroon et al, 2003). So the secondary source of infection was considered as oral cavity.…”
Section: Role Of Micro Organism In Aphthous Ulcer Helicobacter Pylorimentioning
confidence: 99%
“…Histological similarities are shown between gastric and oral ulcers (21,26,27). In recent years, H. pylori has been proposed to be one of the important etiological agents in the pathogenesis of RAS (21,(26)(27)(28)(29)(30)(31). It has been showed that patients with recurrent oral ulcerations appear to suffer from active H. pylori infection in a high percentage up to 70.8% of cases (21).…”
Section: Introductionmentioning
confidence: 98%